SOME POPULATION PARAMETERS AND EXPLOITATION STATUS OF FOURFINGER THREADFIN (Eleutheronema tetradactylum Shaw, 1804) IN TARAKAN WATERS, NORTH KALIMANTAN - Tirtadanu Tirtadanu; Umi Chodrijah (Research Center for Fisheries, 2018)
Information on exploitation status of fourfinger threadfin (Eleutheronema tetradactylum Shaw, 1804) is important for sustainable gillnet fisheries management in Tarakan, North Kalimantan waters. In an attempt of providing scientific data and information on the exploitation status of this species, a research work was conducted from January to November 2016 in Selumit landing place. Fish sampling was done by trained enumerator on bottom gillnet catches landed through semi-regular observation. A total of 1964 specimens were collected and measured. The results showed that the size ranged between 16-70 cmFL with an average of 37.72 ± 0.36 cmFL. The length at first captured (Lc) of about 38.5 cmFL, was smaller than the length at first mature of female (Lm) of 39.6 cmFL. The growth pattern was negative allometry. By applying von Bertalanffy growth model, it was found that growth model for this species was L(t)=75,8(1-e0,3(t+0,035)). Exploitation rate (E) was 0,47. It showed that the exploitation status of fourfinger threadfin in Tarakan Waters was still sustainable.